О постмариупольских / квитнянских погребениях в каменных гробницах - Тесленко, Д. Л. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryD. Teslenko. About the post-Mariupol/Kvityana burials in the stone tombsIn the paper the problem of cultural attributation of the Late Eneolithic “stretched” burials in the stone tombs concentrated on the territory between the Dnieper and Ingulets rivers is analyzed. The author comes to a conclusion that the stone constructions (stone tombs, cromlechs, stelaes) are overcultural feature. Stone tombs as a feature of burial rite correlated with increased labor expenses and prestigious things. In the author’s opinion in these tombs the persons with high social status are buried.During the period synchronous the Tripolie C II stage the integration of various cultural groups, such as Lover Mikhailovka, post-Mariupol, post-Stog, took place on this territory. But the process of formation of new cultural phenomenon was not completed. According the author only the some parts of ancient population were included in this process. The elite of steppe population save the “clear” features of rite.